Possible Involvement of Ghost Introgressions in the Striking Diversity of Vomeronasal Type 1 Receptor Genes in East African Cichlids - Shunsuke Taki; Zicong Zhang; Mitsuto Aibara; Tatsuki Nagasawa; Masato Nikaido (Ecology and Evolution)
ABSTRACT Cichlids that have undergone adaptive radiation are genetically close but exhibit extreme ecological and morphological diversity, making them useful for understanding speciation mechanisms. Vomeronasal type 1 receptors (V1R) are highly conserved among teleost fish at the amino acid sequence level and are believed to play a fundamental role in reproduction. We previously reported the surprisingly high sequence diversity of V1Rs among certain cichlid species, suggesting a possible role for V1Rs in their speciation. In this study, we investigated the process of evolutionary diversification of all 6 V1Rs (V1R1–6) by using the genome data of 528 cichlid species, encompassing nearly all lineages. In the case of V1R2, two highly divergent alleles (1.17%: variant sites/coding sequence [CDS] length) without recombination were preserved and shared among cichlids found in all of the East African Great Lakes. In the case of V1R6, numerous highly variable alleles that could be derived from multiple recombination events between two highly divergent alleles (1.39%: variant sites/CDS length) were found among the Lake Victoria cichlids. Additionally, we identified highly divergent alleles of V1R1 within the tribe Tropheini, and of both V1R3 and V1R6 within Trematocarini and Ectodini. However, despite extensive investigations, we could not identify the source lineages for these introgressions, implying that they may have become extinct. This study revealed the potential role of introgression in explaining the remarkable diversity of V1Rs in East African cichlids.